DETERMINAN TINGKAT BAGI HASIL DEPOSITO MUDHARABAH PERBANKAN SYARIAH DI INDONESIA - Huzein Satrio Prasetyawan; Imron Mawardi (Universitas Airlangga, 2019)
The purpose of this research is to analyze the effect of Return On Assets, SBIS, IPI, and Exchange Rate toward the rate of return mudharabah deposits islamic bank industries in Indonesia start from January 2012 until December 2017. This research use quantitative approach. The analysis method used in this research is Vector Error Correction Model. This research used saturation sampling, the data in this study are secondary data obtained from OJK, BI, and BPS. The results showed that Return On Assets, IPI, and Exchange Rate have a significant effect on the profit sharing rate of mudharabah deposits in the long term and have no significant effect in the short term. While the SBIS variable does not significantly influence the level of profit sharing of mudharabah deposits in the long and short term. Then the biggest influence that influenced the development of Islamic banks in Indonesia in the 2012-2017 research period was the exchange rate.Keywords : Islamic Banking, ROA, SBIS, IPI, Exchange Rate, Rate of Return Deposito Mudharabah, Vector Error Correction Model.